1 - Negation and Affirmation: a critique of sociology in South Africa - Bongani Nyoka, (African Sociological Review, 2014)
This paper critically evaluates the epistemological basis of the academic discipline of sociology in South Africa. In particular, it contextualises, and therefore subjects to critical scrutiny, the assumptions made (and not made) by South African sociologists in their writings about the discipline of sociology in South Africa. Secondly, it seeks to make an epistemic intervention on the current debates on epistemological decolonisation of the social sciences in the South African academy. The issues raised in the paper no doubt go beyond the South African academy and speak to issues raised by sociologists in other parts of the African continent and in the Third World generally.